Effectiveness of multidisciplinary care for Parkinson's disease: A randomized, controlled trial. Issue 5 (19th November 2012) - van der, Marjolein A.; Bloem, Bastiaan R.; Borm, George F.; Overeem, Sebastiaan; Munneke, Marten; Guttman, Mark
<x xml:space="preserve">Abstract</x> Multidisciplinary care is considered an optimal model to manage Parkinson's disease (PD), but supporting evidence is limited. We performed a randomized, controlled trial (RCT) to establish whether a multidisciplinary/specialist team offers better outcomes, compared to stand‐alone care from a general neurologist. Patients with PD were randomly allocated to an intervention group (care from a movement disorders specialist, PD nurses, and social worker) or a control group (care from general neurologists). Both interventions lasted 8 months. Clinicians and researchers were blinded for group allocation. The primary outcome was the change in quality of life (Parkinson's Disease Questionnaire; PDQ‐39) from baseline to 8 months. Other outcomes were the UPDRS, depression (Montgomery‐Asberg Depression Scale; MADRS), psychosocial functioning (Scales for Outcomes in Parkinson's disease‐Psychosocial; SCOPA‐PS), and caregiver strain (Caregiver Strain Index; CSI). Group differences were analyzed using analysis of covariance adjusted for baseline values and presence of response fluctuations. A total of 122 patients were randomized and 100 completed the study (intervention, n = 51; control, n = 49). Compared to controls, the intervention group improved significantly on PDQ‐39 (difference, 3.4; 95% confidence interval [CI]: 0.5–6.2) and UPDRS motor scores (4.1; 95% CI: 0.8–7.3). UPDRS total score (5.6; 95% CI: 0.9–10.3), MADRS (3.7; 95% CI: 1.4–5.9), and SCOPA‐PS (2.1; 95% CI: 0.5–3.7) also improved significantly. This RCT gives credence to a multidisciplinary/specialist team approach. We interpret these positive findings cautiously because of the limitations in study design. Further research is required to assess teams involving additional disciplines and to evaluate cost‐effectiveness of integrated approaches. © 2012 Movement Disorder Society